MicroShunt versus trabeculectomy for surgical management of glaucoma: a retrospective analysis - Fu, MX; Normando, EM; Luk, SMH; Deshmukh, M; Ahmed, F; Crawley, L; Ameen, S; Vig, N; Cordeiro, MF; Bloom, PA (MDPI, 2022)
This case-control study aims to compare the efficacy, safety, and postoperative burden of MicroShunt versus trabeculectomy. The first consecutive cohort of MicroShunt procedures (n = 101) was matched to recent historical trabeculectomy procedures (n = 101) at two London hospital trusts. Primary endpoints included changes in intraocular pressure (IOP) and glaucoma medications. Secondary outcome measures included changes in retinal nerve fibre layer (RNFL) thickness, rates of complications, further theatre interventions, and the number of postoperative visits. From the baseline to Month-18, the median [interquartile range] IOP decreased from 22 [17–29] mmHg (on 4 [3–4] medications) to 15 [10–17] mmHg (on 0 [0–2] medications) and from 20 [16–28] mmHg (on 4 [3–4] medications) to 11 [10–13] mmHg (on 0 [0–0] medications) in the MicroShunt and trabeculectomy groups, respectively. IOP from Month-3 was significantly higher in the MicroShunt group (p = 0.006), with an increased number of medications from Month-12 (p = 0.024). There were greater RNFL thicknesses from Month-6 in the MicroShunt group (p = 0.005). The rates of complications were similar (p = 0.060) but with fewer interventions (p = 0.031) and postoperative visits (p = 0.001) in the MicroShunt group. Therefore, MicroShunt has inferior efficacy to trabeculectomy in lowering IOP and medications but provides a better safety profile and postoperative burden and may delay RNFL loss.